The Role of Depression and Social Adjustment in Fibromyalgia Syndrome - Bilgici, A.; Akdeniz, O.; Güz, H.; Ulusoy, H. (My University, 2005)
Objective: To investigate the relationship between depression and clinical symptoms in subjects with fibromyalgia syndrome (FS), and to compare social adjustment and frequency of depression with healthy controls. Materials and methods: Thirty-seven women, aged 18-55 years, diagnosed as FS according to 1990 American College of Rheumatology criteria were included in this study. The diagnosis of depression was made according to DSM IV criteria. Psychological status was assessed with the Hamilton Depression Scale and the Hamilton Anxiety Scale. The Social Adjustment Scale Self-Report was used for the evaluation of social adjustment. Clinical variables included visual analog scale for pain, fatigue, sleep problems and patients' estimate of health status. Total myalgic score was assessed using a 0-3 scale for each tender point. Results: The rate of concurrent depression in FS patients was significantly greater than healthy controls (p<0.001). Twelve patients (32%) received a concurrent DSM IV diagnosis of depressive disorder, where 25 patients (68%) were not clinically depressed. There was no statistically significant difference between the depressed and non-depressed patients in clinical parameters such as pain, fatigue, sleep disturbance, number of tender points and in social functions and disability scores. On the other hand, the patients with FS showed significantly poorer social adjustment compared to normal controls (p<0.001). Additionally, the patients with FS had significantly higher depression and anxiety scores than controls (p<0.01 and p<0.001, respectively). Conclusion: Our results indicate that concurrent depressive disorders are prevalent in FS and that may be independent from the cardinal features of FS. However, patients with FS exhibit significant decline in social adjustment.
Fibromiyalji Sendromunda Depresyon ve Sosyal Uyumun Rolü
Keywords: Depression; Fibromyalgia Syndrome; Psychological Status; Social Adjustment